Karakterisasi Zona Sliding Di Perbukitan Ranggawulung Subang Dengan Metoda Geolistrik Tahanan Jenis - Susanto, Kusnahadi; Zaenudin, Ahmad (BERKALA FISIKA, 2010)
Subang Ranggawulung Hills is a road connecting Bandung- Subang which is landslide-prone. Landslides have occurred in the area and now the potential for ground movement is still visible which is characterized by crack and wave roads and buildings sideway. This study characterizes the sliding zone and the direction of movement of ground geoelectric resistivity method. Geoelectrical resistivity method to detect the existence of a sliding zone of the layer surface lapsed causes that caused Landslides. Of geoelectric resistivity cross-section indicates that the contact area between the layers with a certain slope at a depth of about 3-10 m below ground surface. Fields marked with a contact layer of low resistivity value of about 5-10 m which is consistent on all tracks. By observing these results can be seen that the hills Ranggawulung potential for the occurrence of landslides, although slow moving. Key words: landslides, low resistivity